Paradoxical Roles of the Neutrophil in Sepsis: Protective and Deleterious - Sônego, Fabiane; Castanheira, Fernanda Vargas e Silva; Ferreira, Raphael Gomes; Kanashiro, Alexandre; Leite, Caio Abner Vitorino Gonçalves; Nascimento, Daniele Carvalho; Colón, David Fernando; Borges, Vanessa de Fátima; Alves-Filho, José Carlos; Cunha, Fernando Queiróz (Frontiers in Immunology, 2016)
Sepsis, an overwhelming inflammatory response syndrome secondary to infection, is one of the costliest and deadliest medical conditions worldwide. Neutrophils are classically considered to be essential players in the host defence against invading pathogens. However, several investigations have shown that impairment of neutrophil migration to the site of infection, also referred to as neutrophil paralysis, occurs during severe sepsis, resulting in an inability of the host to contain and eliminate the infection. On the other hand, the neutrophil antibacterial arsenal contributes to tissue damage and the development of organ dysfunction during sepsis. In this review, we provide an overview of the main events in which neutrophils play a beneficial or deleterious role in the outcome of sepsis.